Faktor Penentu Tingkat Kepuasan Kerja Karyawan (Studi Kasus di PT. Karya Makmur Bahagia, Kabupaten Kotawaringin Timur, Kalimantan Tengah) - Ismiasih Ismiasih; Kusmiati Kusmiati; Fahmi Wiryamarta Kifli (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
Employees are an important asset for the company. Every employee is required to be able to work optimally in realizing company goals. Therefore, employee satisfaction at work must be fulfilled. This study aims to determine: (1) the level of job satisfaction of employees at PT. Karya Makmur Bahagia, and (2) the determinants of employee satisfaction levels at PT. Happy Prosperous Works. The population in this study are employees of PT. Karya Makmur Bahagia with a total population of 106 employees. 52 samples were selected which were determined using the Slovin formula. Data collection was carried out by observation, questionnaires and documentation. Data were analyzed using multiple linear regression estimated by the OLS (Ordinary Least Square) method. The results of this study indicate that: (1) the level of job satisfaction of employees at PT. Karya Makmur Bahagia is included in the satisfied category. (2) work relations, work facilities, work motivation, salary/income have a significant and positive influence on employee job satisfaction at PT Karya Makmur Bahagia